Endophytic fungi from Pecteilis susannae (L.) Rafin (Orchidaceae), a threatened terrestrial orchid in Thailand - Ruangwut Chutima (2018)
Eight endophytic fungi were isolated from roots of the threatened terrestrial orchid, Pecteilis susannae (L.) Rafin. Phylogenetic analysis based on an alignment of internal transcribed spacer regions of nuclear rDNA indicated that seven isolates belonged to the genus Epulorhiza and one to Fusarium. All fungal isolates were cultured with orchid seeds collected from three field sites near Doi Suthep-Pui National Park, Chiang Mai, Thailand. Seed germination and protocorm development were evaluated up to 70 days after sowing. Percent symbiotic seed germination was highest (86.2%) when seeds were cultured with Epulorhiza (CMU-Aug 013). The protocorm development was the most advanced up to stage 2, continued embryo enlargement, or rupture of the testa, and the highest percentage was 17.8% when seeds were cultured with Epulorhiza (CMU-Aug 007). Without fungi, seed germination and protocorm development were 62.1% and 11.1%, respectively. The dependency of P. susannae on fungal symbionts for early seedling development is yet to be determined. Optimizing seed germination and seedling fitness will assist the conservation of this threatened orchid in Thailand. © 2010 Springer-Verlag.